Pertumbuhan Bibit Kakao (Theobroma Cacao L.) Klon ICCRI 03 Dan Mcc 01 Pada Beberapa Lama Penyimpanan Benih - Agusta, Fennaldy Bambang; Fatimah, Titien; Rahmawati, Rahmawati (Agropross : National Conference Proceedings of Agriculture, 2022)
Cocoa seeds are recalcitrant seeds that have an inability to store long enough. As a result of storage, cocoa seeds can experience seed deterioration as well as in the growth process in nurseries. To find out that cocoa seeds that have been stored can grow well in nurseries, it is necessary to do seedling based on cocoa seeds that have been stored. This research was carried out at the Seed Production Technology Laboratory, from August to October 2020, Wire House, and the Jember State Polytechnic Soil Laboratory from October 2020 to March 2021. The design used was a Factorial Randomized Design (RAKF) consisting of 2 factors and 4 replicates. The first factor is clones (K) consisting of 2 types, namely K1 = ICCRI 03: K2 = MCC 01, and the second factor is Storage Time (P) with 4 levels, namely: P0 = Directly planted (control) : P1 = Stored 5 Days : P2 = Stored 10 Days : P3 = Stored 15 Days. Parameters observed were seedling stem diameter, seedling height, number of seedling leaves, seedling wet weight, seedling dry weight and seedling root length. The results showed that the differences in clones had a very significant effect on the observation parameters of seedling height, number of seedling leaves, seedling stem diameter, wet and dry weight of seeds on stored seeds. The storage time treatment had a very significant effect on the observation parameters of seedling height, number of seedling leaves, and seedling stem diameter. And the interaction between clones and storage time had a very significant effect on seedling height and number of seedling leaves.